Providing Legal Protection for Holders of Electronic Land Certificates - Dini Ernawati, Asri Wijayanti, Fajar Rachmad Dwi Miarsa (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Digital transformation in Indonesia’s land administration is being realized through the implementation of Electronic Land Certificates, aiming to enhance efficiency, transparency, and legal certainty. This study explores the evidentiary strength and legal protection afforded to holders of electronic land certificates. Using a normative legal approach, the analysis draws on relevant legal frameworks, including the Electronic Information and Transactions Law, the Consumer Protection Law, and Ministry Regulation No. 3 of 2023 of the National Land Agency/Agrarian Affairs and Spatial Planning. The findings indicate that electronic land certificates are legally valid as evidence in court, safeguarded by data security regulations, and supported by encryption technologies, electronic signatures, and QR codes. Legal protection is provided through both preventive and repressive measures, covering rights to information, personal data security, and dispute resolution mechanisms. However, several challenges persist, especially in regard to digital literacy and infrastructure, and system integration. In conclusion, the successful adoption of electronic land certificates depends on regulatory coherence, technological readiness, and active public participation to establish a secure and reliable digital land administration system